Graded porous metal selenide for water decomposition reaction as well as preparation method and application of graded porous metal selenide

By using a continuous channel adjustable graded porous metal selenide catalyst during water electrolysis, the sintering and aggregation problems of electrocatalysts in the high-temperature derivation process in the prior art are solved, and catalytic activity and stability are improved, and the catalytic activity and stability are reduced. It has good industrial application prospects.

CN119430091APending Publication Date: 2025-02-14OCEAN UNIV OF CHINA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411562283.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing electrocatalysts have problems in sintering and agglomeration during high-temperature derivation during water electrolysis, which hinders the diffusion and release of mass transfer and oxygen bubbles of the electrolyte, resulting in insufficient catalytic activity and stability.

Method used

A continuous porous metal selenide with adjustable continuous pore channels is used to synthesize three-dimensional graded porous materials with composite frames by directed freeze-drying to avoid agglomeration of MOFs during sintering, and undergo high-temperature selenization treatment under inert gas to prepare A catalyst with uniformly orientated micron-scale pores is produced.

Benefits of technology

The catalyst channel structure is achieved, the charge transfer and mass transfer efficiency is improved, bubbles are avoided invasion of active sites, significantly improved the catalytic activity and stability of OER and HER, and at the same time, the catalyst cost is reduced, and it has good industrial application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430091A_ABST
    Figure CN119430091A_ABST
Patent Text Reader

Abstract

The invention discloses a graded porous metal selenide for a water decomposition reaction and a preparation method and application thereof.The preparation method comprises the steps that a mixed solution of metal-organic frameworks (MOFs), graphene oxide (rGO), carbon nanotubes (CNTs) and nanocellulose (CNFs) is subjected to directional freeze drying, and a three-dimensional porous carbon framework loaded with the MOFs is obtained; and then carrying out high-temperature selenylation treatment on the obtained three-dimensional porous framework to form the electrocatalytic composite material consisting of a carbon skeleton and selenide on the carbon skeleton. In the process, the MOFs can be uniformly dispersed on a carbon skeleton composed of rGO, CNTs and CNFs, so that the agglomeration phenomenon of the MOFs can be reduced in the selenylation process, and the MOFs are uniformly dispersed to expose more active sites; and meanwhile, the directional pore channels are beneficial to overflow of bubbles in the water decomposition reaction process, so that active sites are prevented from being occupied by accumulation of the bubbles, and the electro-catalytic performance of the selenide is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of oxygen evolution reaction catalysts, and specifically relates to a graded porous metal selenide for water decomposition reaction, and a preparation method and application thereof. Background Art

[0002] The energy system based on fossil energy is the foundation of modern social development. The large-scale burning of traditional fossil fuels has brought about a series of problems such as ecological environmental damage and energy resource shortages, posing a serious threat to the sustainable development of human society. Therefore, people are eager to find renewable energy sources such as wind and solar energy. However, these sustainable energy sources are usually intermittent and cannot provide energy stably and continuously, resulting in energy waste. Therefore, it is crucial to directly convert the electricity generated by renewable energy into high-value-added chemicals such as hydrogen energy as an energy carrier, fuel or raw material. By establishing an advanced energy storage and supply system, reducing dependence on fossil energy, forming a technical system with renewable energy as the main energy source, and realizing an efficient, clean, and low-carbon energy industrial system.

[0003] Hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) are key reactions in these electrochemical processes, occurring at the cathode and anode, respectively, to maintain the overall balance of the electrochemical system. Due to its high overpotential and kinetic limitations, water electrolysis usually requires efficient electrocatalysts to improve the efficiency of the above energy conversion and storage processes. Precious metal-based catalysts are typical OER catalysts (such as IrO2 and RuO2) and HER catalysts (such as Pt / C), but their scarcity and high cost limit their application. Therefore, the development of low-cost and high-performance water electrolysis catalysts is of great significance to the basic research and practical application of electrochemical water splitting.

[0004] Compared with organic-inorganic hybrid materials and coordination polymers, metal organic frameworks (MOFs) highlight the porous characteristics and periodic arrangement properties of the material, and have broad application prospects in the fields of catalysis, adsorption and separation. Although MOF provides a wide range of microporous and mesoporous structures for its derived transition metal electrocatalysts, thereby providing sufficient active sites, its high-temperature derivatization processes (such as selenization, nitridation and phosphiding) often face the challenges of sintering and agglomeration. In addition, at the micron scale, the sintering and agglomeration of MOF particles will hinder the mass transfer of electrolytes and the diffusion and release of oxygen bubbles. Therefore, it is imperative to improve the derivatization strategy of MOF-based water splitting reactants while considering the influence of micron-scale size to achieve efficient electrolysis of water. Summary of the invention

[0005] The purpose of the present invention is to provide a graded porous metal selenide with adjustable continuous pores and a preparation method and application thereof. The selenide is used for water electrolysis under alkaline conditions and has the characteristics of adjustable pores, which meets the requirements of industrial water electrolysis.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] A hierarchical porous metal selenide for water decomposition reaction, wherein under a high-magnification electron microscope, the metal selenide as a whole presents a highly oriented pore structure, and the metal selenide is loaded on the pores;

[0008] The metal selenide includes at least one of iron selenide, nickel selenide, cobalt selenide, zinc selenide and copper selenide.

[0009] The present application also provides a method for preparing the hierarchical porous metal selenide as described above, comprising the following steps:

[0010] (a) Preparation of MOFs, wherein the MOFs include MOF-74, ZIF-8, ZIF-67 and PBA (Prussian blue and its analogs).

[0011] (b) providing a first solution formed by rGO, CNTs, CNFs and a water solvent, mixing the MOFs synthesized in step (a) with the first solution, and then directionally freezing the solution to obtain a hierarchical porous precursor with adjustable continuous pores loaded with MOFs;

[0012] The precursor is freeze-dried by a freeze dryer to remove moisture from the precursor and retain the oriented pores;

[0013] (c) Then, the freeze-dried material in step (b) is subjected to selenization treatment under an inert gas to obtain a graded porous metal selenide with adjustable continuous pores.

[0014] The inert gas includes any one of nitrogen and argon.

[0015] Preferably, the specific method for preparing MOFs in step (a) is: providing a metal salt, an organic ligand and a solvent to form a mixed solution, synthesizing MOFs by a one-pot method, and then collecting MOFs after centrifugation, washing and drying;

[0016] The metal salt includes one or two of nickel salt, iron salt, cobalt salt and zinc salt;

[0017] The organic ligand includes one of 2-methylimidazole, 4-methylimidazole and 1,2,4,5-benzenetetracarboxylic acid;

[0018] The solvent includes at least one of methanol, anhydrous ethanol and deionized water.

[0019] Preferably, in step (a), the concentrations of the metal salt and the organic ligand are both 0.01 to 0.1 mol / L;

[0020] The centrifugation and washing times are 3 to 5 times;

[0021] The centrifugation and washing solvents are water and ethanol respectively;

[0022] The drying temperature is 50-80°C.

[0023] Preferably, in step (b), the concentration of the first solution is adjusted to ultimately obtain metal selenides with different pore diameters, and the mass fraction of rGO, CNTs and CNFs in the first solution is 0.35-0.75%.

[0024] Preferably, in step (b), the mass ratio of rGO, CNFs, CNTs and MOFs is 1:1:2:(4-6).

[0025] Preferably, in step (b), the method for uniform mixing is mechanical stirring for 30 to 50 minutes, followed by ultrasonication for 20 to 30 minutes.

[0026] Preferably, in step (b), the mold for directional freeze-drying is a polytetrafluoroethylene mold with a mold size of 2 cm×5 cm, and the freezing source is liquid nitrogen.

[0027] Preferably, in step (c), the selenium source during selenization is selenium powder, and the mass used is 100 to 400 mg;

[0028] The selenization temperature is 350-450°C;

[0029] The selenization time is 2 to 4 hours;

[0030] The heating rate is 3-5°C / min;

[0031] The flow rate of the inert gas flow is 50 to 200 mL / min.

[0032] In addition, the present application also provides an application of the graded porous metal selenide as described above in water electrolysis oxygen reaction.

[0033] Compared with the prior art, the present invention has the following beneficial effects:

[0034] (1) The present invention provides a method for preparing a hierarchical porous metal selenide with adjustable continuous pores. A three-dimensional hierarchical porous material with a composite framework is synthesized by simple directional freeze-drying to avoid the agglomeration of MOFs during the sintering process. A simple and universal synthesis strategy is developed to produce a unique nanocomposite framework structure with adjustable pores, while promoting charge transfer and mass transfer. Compared with directly selenized MOFs, the morphology of selenized MOFs on the composite framework can be well preserved.

[0035] (2) The hierarchical porous metal selenide prepared by the present invention has uniformly oriented micron-sized pores. The hydrogen bonding between rGO and CNF improves the mechanical strength of the oriented pores. CNT makes the material have good electrical conductivity, which not only exposes more active sites of the metal selenide, but also provides a fast channel for the overflow of bubbles, avoiding the invasion of bubbles on the active sites, and improving the catalytic OER and HER catalytic activity and catalytic stability.

[0036] (3) The hierarchical porous metal selenide prepared by the present invention can be applied to various MOFs scenarios, has good universality, and the metal used is a transition metal with low cost and abundant reserves in nature, which reduces the cost of the catalyst. At the same time, the preparation method is simple in preparation process and easy to operate, and has good industrial application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] In order to more clearly illustrate the specific implementation of the present invention or the technical solution in the prior art, the drawings required for use in the specific implementation or the description of the prior art will be briefly introduced below.

[0038] Figure 1 is the cross-sectional morphology of the graded porous metal selenide in Example 1 of the present invention, wherein: Figure 1 (a) is the cross-sectional morphology of Example 1, and (b) is the longitudinal sectional morphology of Example 1;

[0039] Figure 2 1 is a comparison of high-resolution scanning electron microscope images of Example 1 of the present invention and Comparative Example 1, wherein (a) is a scanning electron microscope image of Example 1, and (b) is a scanning electron microscope image of Example 1;

[0040] Figure 3 The X-ray diffraction patterns of Example 1 and Comparative Example 1 of the present invention;

[0041] Figure 4 Polarization curves of HER performance of Examples 1 to 3 of the present invention and Comparative Examples 1 to 3.

[0042] Figure 5 Polarization curves of OER performance of Examples 1 to 3 of the present invention and Comparative Examples 1 to 3.

[0043] Figure 6 This is a constant current stability test curve of Example 1 of the present invention. DETAILED DESCRIPTION

[0044] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be construed as limiting the scope of the present invention. If specific conditions are not specified in the examples, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0045] According to a first aspect of the present invention, there is provided a method for preparing a layered porous selenide catalyst, comprising the following steps:

[0046] (a) providing a metal salt, an organic ligand and a solvent to form a mixed solution, synthesizing MOFs by a one-pot method, and then centrifuging and washing multiple times, and collecting the MOFs material after drying;

[0047] Wherein, the metal salt includes at least one of nickel salt, iron salt, cobalt salt, zinc salt and copper salt, the organic ligand includes at least one of 2-methylimidazole, 4-methylimidazole and 1,2,4,5-benzenetetracarboxylic acid, the solvent includes one or more of methanol, anhydrous ethanol and deionized water, and the MOFs include MOF-74, ZIF-8, ZIF-67 and PBA.

[0048] (b) providing a first solution formed by rGO, CNTs, CNFs and a water solvent, uniformly mixing the MOFs synthesized in step (a) with the first solution, and then directionally freezing to obtain a hierarchical porous precursor loaded with MOFs;

[0049] The precursor is freeze-dried by a freeze dryer to remove moisture from the precursor and retain the oriented pores;

[0050] (c) The freeze-dried material is then subjected to a high-temperature selenization treatment under an inert gas to obtain a graded porous metal selenide.

[0051] Wherein, the inert gas includes any one of nitrogen and argon.

[0052] Specifically, in step (a), the concentrations of the transition metal salt and the organic ligand are both 0.01-0.1 mol / L, the number of centrifugal washings is 3-5 times, the centrifugal washing solvents are water and ethanol, and the drying temperature is 50-80°C.

[0053] Specifically, in the step (b), catalysts with different pore sizes can be finally obtained by adjusting the concentration of the first solution, and the mass fraction of the rGO, CNTs and CNFs in the first solution is 0.35-0.75%.

[0054] Specifically, in the step (b), the mass ratio of rGO, CNFs, CNTs and MOFs is 1:1:2:(4-6).

[0055] Specifically, in the step (b), the method for uniform mixing is mechanical stirring for 30 to 50 minutes, followed by ultrasonication for 20 to 30 minutes.

[0056] Specifically, in the step (c), the selenium source during selenization is selenium powder, the mass used is 100-400 mg, the selenization temperature is 350-450° C., the selenization time is 2-4 h, the heating rate is 3-5° C. / min, and the flow rate of the inert gas flow is 50-200 mL / min.

[0057] The graded porous metal selenide with adjustable continuous pores prepared by the present invention can obtain a graded porous metal selenide catalyst with uniform pore sizes and uniformly dispersed MOFs, which is applied in the field of water decomposition reactions.

[0058] The present invention will be further described below in conjunction with specific embodiments and comparative examples.

[0059] Example 1

[0060] The method for preparing the graded porous metal selenide with adjustable continuous pores provided in this embodiment comprises the following steps:

[0061] a) Dissolve NiCl2·6H2O (30 mmol) and Na3C6H5O7·2H2O (45 mmol) in 500 mL of deionized water, stir for 20 min, and stir evenly to form solution A; dissolve K3(Fe(CN)6) (20 mmol) in 500 ml of deionized water, stir for 20 min, and stir evenly to form solution B; pour solution B into solution A, continue stirring for 30 min to disperse evenly, age at room temperature for 12 h, wash three times with anhydrous ethanol and deionized water respectively, and dry in an oven at 60°C overnight to obtain PBA particles.

[0062] b) rGO (75 mg), CNTs (75 mg) and CNFs (12 g, 1.27 ωt.%) were dissolved in 28 mL of deionized water and mechanically stirred for 30 min to form a solution C. The obtained PBA particles (400 mg) were then added to the solution C and mechanical stirring was continued for 30 min. The mixed solution was then ultrasonicated for 20 min to remove bubbles in the mixed solution. 5 mL of the ultrasonicated solution was taken out and poured into a customized polytetrafluoroethylene mold (2 cm × 5 cm). The bottom of the mold was a customized copper bracket to provide a unidirectional temperature gradient. The copper bracket at the bottom of the polytetrafluoroethylene was placed in liquid nitrogen to quickly freeze the solution. After freezing, it was quickly placed in a freeze dryer and freeze-dried for 48 hours to obtain a layered porous precursor loaded with PBA particles.

[0063] c) The layered porous precursor loaded with PBA particles was placed in a tubular furnace, selenium powder (100 mg) was placed in the upstream porcelain boat, and the precursor was placed in the downstream porcelain boat. The temperature was raised to 350°C at a heating rate of 5°C / min in a nitrogen atmosphere, and high-temperature selenization was performed for 2 hours with an inert gas flow rate of 200 mL / min to obtain a graded porous metal selenide.

[0064] Example 2

[0065] a) Zn(NO3)2·6H2O (10 mmol) and Co(NO3)2·6H2O (10 mmol) were dissolved in 100 mL of deionized water to form solution A, 2-methylimidazole (700 mmol) was dissolved in 100 mL of deionized water to obtain solution B, A was poured into B and rapidly stirred for 30 min, followed by multiple centrifugal washing with deionized water, and dried at 60°C for 12 h to obtain ZnCo-ZIF-8 particles.

[0066] b) rGO (75 mg), CNTs (75 mg) and CNFs (12 g, 1.27 ωt.%) were dissolved in 28 mL of deionized water and mechanically stirred for 30 min to form a solution C. The obtained ZnCo-ZIF-8 particles (400 mg) were then added to the solution C and mechanical stirring was continued for 30 min. The mixed solution was then ultrasonicated for 20 min to remove bubbles in the mixed solution. 5 mL of the ultrasonicated solution was taken out and poured into a customized polytetrafluoroethylene mold (2 cm × 5 cm). The bottom of the mold was a customized copper bracket to provide a unidirectional temperature gradient. The copper bracket at the bottom of the polytetrafluoroethylene was placed in liquid nitrogen to quickly freeze the solution. After freezing, it was quickly placed in a freeze dryer and freeze-dried for 48 hours to obtain a layered porous precursor loaded with ZnCo-ZIF-8 particles.

[0067] c) The hierarchical porous precursor loaded with ZnCo-ZIF-8 particles was placed in a tubular furnace, selenium powder (100 mg) was placed in the upstream porcelain boat, and the precursor was placed in the downstream porcelain boat. The temperature was raised to 350°C at a heating rate of 5°C / min in a nitrogen atmosphere, and high-temperature selenization was performed for 2 hours with an inert gas flow rate of 200 mL / min to obtain a hierarchical porous metal selenide.

[0068] Example 3

[0069] The method for preparing the graded porous metal selenide with adjustable continuous pores provided in this embodiment comprises the following steps:

[0070] a) CH3C3H3N2 (50 mmol) and Co(NO3)2·6H2O (25 mmol) were stirred in 20 mL of methanol solution for 1 hour to form a uniform suspension. The resulting uniform mixture solution was then placed at room temperature for 24 hours, the purple product was repeatedly washed with methanol several times, collected by centrifugation, and dried at 60°C for 12 hours to obtain ZIF-67 powder.

[0071] b) rGO (75 mg), CNTs (75 mg) and CNFs (12 g, 1.27 ωt.%) were dissolved in 28 mL of deionized water and mechanically stirred for 30 min to form a solution C. The obtained ZIF-67 particles (400 mg) were then added to the solution C and mechanical stirring was continued for 30 min. The mixed solution was then ultrasonicated for 20 min to remove bubbles in the mixed solution. 5 mL of the ultrasonicated solution was taken out and poured into a customized polytetrafluoroethylene mold (2 cm × 5 cm). The bottom of the mold was a customized copper bracket to provide a unidirectional temperature gradient. The copper bracket at the bottom of the polytetrafluoroethylene was placed in liquid nitrogen to quickly freeze the solution. After freezing, it was quickly placed in a freeze dryer and freeze-dried for 48 hours to obtain a layered porous precursor loaded with ZIF-67 particles.

[0072] c) The hierarchical porous precursor loaded with ZIF-67 particles was placed in a tubular furnace, selenium powder (100 mg) was placed in the upstream porcelain boat, and the precursor was placed in the downstream porcelain boat. The temperature was raised to 350°C at a heating rate of 5°C / min in a nitrogen atmosphere, and high-temperature selenization was performed for 2 hours with an inert gas flow rate of 200 mL / min to obtain a hierarchical porous metal selenide.

[0073] Comparative Example 1

[0074] After collecting the PBA particles obtained in step (a) of Example 1, the PBA is directly selenized without mixing with CNTs and CNFs. The selenization method is the same as that of Example 1 to obtain a directly selenized PBA material.

[0075] Comparative Example 2

[0076] The rGO (75 mg) and CNTs (75 mg) in step (b) of Example 1 were replaced by CNTs (150 mg). The remaining steps and process parameters were the same as those in Example 1.

[0077] Comparative Example 3

[0078] The method of placing selenium powder (100 mg) in the upstream porcelain boat in step c) of Example 1 was replaced by placing no selenium powder in the upstream porcelain boat. The remaining steps and process parameters were the same as those of Example 1.

[0079] In order to verify the technical effects of the embodiments and comparative examples, the following experiments were conducted.

[0080] Product performance test

[0081] Observe the cross-sectional morphology and longitudinal cross-sectional morphology of the hierarchical porous metal selenide in Example 1. Figure 1 As shown. Among them, Figure 1 (a) is the cross-sectional morphology of Example 1, Figure 1 (b) is the longitudinal cross-sectional morphology of Example 1. It can be clearly observed that the synthesized catalyst has well-oriented pores, and the pores are uniform in size.

[0082] Next, the morphologies of Example 1 and Comparative Example 1 were compared. Figure 2 As shown. Among them, Figure 2 (a) is a high-magnification scanning electron microscope image of Example 1, and (b) is a high-magnification scanning electron microscope image of Comparative Example 1. As can be seen from the figure, the PBA particles in Comparative Example 1 have undergone serious agglomeration, while the PBA particles in Example 1 are evenly distributed without agglomeration, and can maintain a good morphology after selenization.

[0083] For the X-ray diffraction patterns in Example 1 and Comparative Example 1, Figure 3 As shown. Figure 3 It can be observed that both Example 1 and Comparative Example 1 have obvious peaks corresponding to iron selenide and nickel selenide, the samples have high crystallinity and no impurity peaks, indicating that the selenide was successfully prepared.

[0084] The catalysts provided in Examples 1-3 and Comparative Examples 1-3 were tested for performance, and the electrochemical properties of the catalysts prepared in Examples 1 and Comparative Examples 4-6 were tested using a standard three-electrode system. The counter electrode was a platinum sheet, the reference electrode was a saturated calomel electrode, and 1M KOH was used as the electrolyte. The working electrode was prepared by a coating method, 5 mg of catalyst, 50 μL of 5.0 ωt.% Nafion solution, and 200 μL of anhydrous ethanol were ultrasonically dispersed to form a uniform slurry, and 50 μL of the slurry was coated on a pretreated nickel foam (1 cm×1 cm) with a micropipette, and dried at room temperature.

[0085] The linear sweep cyclic voltammetry (LSV) of Examples 1-3 and Comparative Examples 1-3 was tested under the same conditions. The experimental results are as follows: Figure 4 , 5 As shown, Example 1 has excellent electrocatalytic water electrolysis performance, wherein the overpotential of the OER polarization curve of Example 1 is 330 mV when the current density reaches 200 mA cm-2, and the overpotential of the HER polarization curve is 160 mV when the current density reaches 200 mA cm-2.

[0086] The catalytic stability of Examples 1-3 was measured using a standard three-electrode system, with Example 1 serving as the anode and cathode, respectively, and the stability of Example 1 was measured using a constant current test (CP) at a current density of 100 mA cm-2. Figure 6 As shown, after 30 hours of testing, the catalytic activity of Example 1 was stably maintained.

Claims

1. A hierarchical porous metal selenide for water decomposition reaction, characterized in that: Under a high-magnification electron microscope, the metal selenide as a whole presents a highly oriented pore structure, and the metal selenide is loaded on the pore; The metal selenide includes at least one of iron selenide, nickel selenide, cobalt selenide, zinc selenide and copper selenide.

2. A method for preparing the hierarchical porous metal selenide according to claim 1, characterized in that: The following steps are involved: (a) preparing MOFs, wherein the MOFs include MOF-74, ZIF-8, ZIF-67 and PBA. (b) providing a first solution formed by rGO, CNTs, CNFs and a water solvent, mixing the MOFs synthesized in step (a) with the first solution, and then directionally freezing the solution to obtain a hierarchical porous precursor with adjustable continuous pores loaded with MOFs; The precursor is freeze-dried by a freeze dryer to remove moisture from the precursor and retain the oriented pores; (c) Then, the freeze-dried material in step (b) is subjected to selenization treatment under an inert gas to obtain a graded porous metal selenide with adjustable continuous pores. The inert gas includes any one of nitrogen and argon.

3. The method for preparing hierarchical porous metal selenide according to claim 2, characterized in that: The specific method for preparing MOFs in step (a) is: providing a metal salt, an organic ligand and a solvent to form a mixed solution, synthesizing MOFs by a one-pot method, and then collecting the MOFs after centrifugation, washing and drying; The metal salt includes one or two of nickel salt, iron salt, cobalt salt and zinc salt; The organic ligand includes one of 2-methylimidazole, 4-methylimidazole and 1,2,4,5-benzenetetracarboxylic acid; The solvent includes at least one of methanol, anhydrous ethanol and deionized water.

4. The method for preparing hierarchical porous metal selenide according to claim 3, characterized in that: In step (a), the concentrations of the metal salt and the organic ligand are both 0.01 to 0.1 mol / L; The centrifugation and washing times are 3 to 5 times; The centrifugation and washing solvents are water and ethanol respectively; The drying temperature is 50-80°C.

5. The method for preparing hierarchical porous metal selenide according to claim 2, characterized in that: In step (b), the concentration of the first solution is adjusted to finally obtain metal selenides with different pore diameters, and the mass fraction of rGO, CNTs and CNFs in the first solution is 0.35-0.75%.

6. The method for preparing hierarchical porous metal selenide according to claim 2, characterized in that: In step (b), the mass ratio of rGO, CNFs, CNTs and MOFs is 1:1:2:(4-6).

7. The method for preparing hierarchical porous metal selenide according to claim 2, characterized in that: In step (b), the method for uniform mixing is mechanical stirring for 30 to 50 minutes, followed by ultrasonication for 20 to 30 minutes.

8. The method for preparing hierarchical porous metal selenide according to claim 2, characterized in that: In step (b), the mold for directional freeze drying is a polytetrafluoroethylene mold with a mold size of 2 cm×5 cm, and the freezing source is liquid nitrogen.

9. The method for preparing hierarchical porous metal selenide according to claim 2, characterized in that: In step (c), the selenium source during selenization is selenium powder, and the mass used is 100 to 400 mg; The selenization temperature is 350-450°C; The selenization time is 2 to 4 hours; The heating rate is 3-5°C / min; The flow rate of the inert gas flow is 50 to 200 mL / min.

10. Use of the hierarchical porous metal selenide according to claim 1 in water electrolysis oxygen reaction.